Protection of foreign investment: a study in international law - Kronfol, Zouhair A. (Leiden: A. W. Sijthoff, 1972)
This book attempt to address the crucial question on how much and how little protection does international law afford to foreign investment. It also deals with one set of measures which are essential for the flow of private capital to the developing countries and problems which such guarantees raise in international law.
Originally presented as the author's thesis, American University, 1970.
Bibliography: p. 171-176.
usc 25/06/18
Loans
Keywords: Investments, Foreign (International law)